Fast Screening Method for Polymorphisms in Exon 9 of the Catalase Gene. - Góth, László; Zabolai, Edit; Nagy, Teréz (Journal of DNA And RNA Research, 2017)
We checked our simple screening technique for detection of the known polymorphism of rs769217, and the two acatalasemic mutations in exon 9 of the catalase gene. This fast and inexpensive method yielded better resolution than those of the standard SSCP. We suppose that the method detects the spontaneously formed single stranded DNAs.
Keywords: Catalase gene mutations; acatalasemia; screening; SSCP